Workforce profile, human resources and client relations of the BPO industry in Iloilo City - Abaygar, Cindy; Artaba, Michelle Veronica; Barrera, Chaldean; Brillantes, Christyn Mae
This research study aimed to describe the workforce profile, human resources, and client relations of the employees of the employees of the BPO industry in Iloilo City to provide valuable information and insights that can aid the management of BPO companies and other related industries in improving the thriving BPO industry in the Philippines. A descriptive research design was used for this study. Specifically, a group-generated questionnaire was given out to 40 employees of different BPO companies in Iloilo City. Purposive sampling was used in choosing the five BPO companies to be studied among the oldest and/or the biggest BPO companies in Iloilo City and convenience sampling was used in selecting the respondents. Moreover, the questionnaire was divided into three parts: Workforce Profile, Human Resources, and Client Relations. Under Workforce Profile, the group has identified two variables: Socioeconomic Characteristics and Technological Knowledge. For Human Resources, the following variables were identified: Compensation, Work environment, and Social Responsibility, and lastly Client Relations had two variables: Productivity and Efficiency. Results revealed that in terms of the socioeconomic characteristics of the workforce profile, majority of the BPO employees are single, have acquired a college degree and are 25 years of age age in average. In terms of technical knowledge, majority of them are given adequate trainings needed for the job by their respective companies. for human resources, majority of the BPO employees believes that they are treated fairly by their employers, and the compensation and benefits recieved by them are appropriate for their work load. As far as social responsibility is concerned, BPO companies provide social sustainability in areas such as respect for human rights, mandatory days off, non-discrimination, and no forced/comulsory labor. These factors produced a client relations assessment that majority of the BPO employees are productive and efficient in doing the tasks assigned to them. To further improve productivity and efficiency of BPO employees to promote better client relations, the following recommendations are suggested: 1) Improved Compensation Program and 2) Productivity and Efficiency Based Time Shifts (P&E) and 3)Skills Enhancement Trainings.